Two Cases of Cutaneous Myopericytoma: A Rare Perivascular Tumor with Distinct Histologic and Immunohistochemical Features - Kim, Jee Woo; Kwon, Hyun Jung; Kim, Min Jae; Huh, Chang Hun (Annals of dermatology, 2023)
KCI Citation Count: 0